Competition Frame on MotoGP Articles: A Cognitive Linguistic Approach - Yessy Purnamasari (Jurnal Bahasa Inggris Terapan, 2018)
This paper is entitled “Competition Frame on MotoGP Articles: A Cognitive Linguistic Approach.” This research is aimed to identify two main points: (1) the elements of the competition frame found in MotoGP articles and (2) to identify the most frequent element that occurs in MotoGP articles. This research employs the syntactic approach and uses the descriptive qualitative method. The siginificance of this study is to give information about the competition frame on sport articles as part of linguistic variety. The result of this research shows there are six elements used on the articles: competition, participant, place, prize, rank and score and value. Then, the most frequent words that occur on the MotoGP articles are dominated by the participant elements (92.85%) and rank and score elements (28.57%).Key words: frame semantic, cognitive linguistics, competition element